Conformational signature of Ishikawa´s reagent using NMR information from diastereotopic fluorines - Andrade, Laize A. F.; Zeoly, Lucas A.; Cormanich, Rodrigo A.; Freitas, Matheus P. (Beilstein Journal of Organic Chemistry, 2019)
The active species of the Ishikawa´s reagent [N,N-diethyl-(1,1,2,3,3,3-hexafluoropropyl)amine] is a fluorinating hexafluoropropylamine used to convert alcohols into alkyl fluorides. On the other hand, it is also an example of model compound useful to probe conformational preferences using spectroscopic information from diastereotopic fluorines. Moreover, the possibility of experiencing both the generalized anomeric and gauche effects makes the Ishikawa´s reagent an ideal choice to study the governing stereoelectronic interactions of the conformational equilibrium of organofluorine compounds. The conformational equilibrium of the Ishikawa´s reagent was analyzed using NMR 3JH,F coupling constant data in different solvents, since the orientation of the diastereotopic fluorines relative to H-2 and F-2 changes with the medium. In nonpolar cyclohexane solvent, the preferred conformation experiences a weaker steric and electrostatic repulsion. The conformational behavior changes in the more polar pyridine solution, where the double fluorine gauche effect takes place, since F-2 is preferably gauche to both diastereotopic fluorines. An analysis of the rotation around the N–C(F2) bond indicates the manifestation of anomeric interactions (nN → σ*C–F), which can be demonstrated by means of 19F chemical shifts. The results were rationalized with the aid of theoretical calculations and natural bond orbital (NBO) analysis, allowing for the evaluation of competing steric, electrostatic and hyperconjugative interactions.
Keywords: anomeric effect; gauche effect; NMR spectroscopy; organofluorine compounds